Internet of Things (IoT) based Smart Agriculture in India: An Overview - Suma, V. (Journal of ISMAC, 2021)
The increasing global population demands improved production to provide food in all sectors, especially in agriculture. Still, at certain periods, demand and supply will not match. Managing and sustaining capital and manpower is still a demanding challenge for improving agricultural production. Smart agriculture is a better option for growing food production, resource management, and labour. This research provides an overview of predictive analysis, Internet of Things (IoT) devices with cloud management, security units for multi-culture in the agriculture sector with considering farmer’s prior experiences. And also highlights the challenges and complications expected while integrating modern technology in the traditional farming practice experience. Based on the statistical and quantitative approaches gives better revolutionary changes in the current agriculture system. Besides, drone activation from IoT encounters crop status and stages, irrigation, plant leaves diseases in the green field. The sensors are activated for various purposes in IoT are discussed. Modern agriculture with state-of-the-art IoT devices and concepts is the main objective of this research. The systematic evaluation provides current and future trends in the agriculture sector.